Antisense Oligonucleotides Targeting Y-Box Binding Protein-1 Inhibit Tumor Angiogenesis by Downregulating Bcl-xL-VEGFR2/-Tie Axes - Kiyoko Setoguchi; Lin Cui; Nobutaka Hachisuka; Sumalee Obchoei; Kentaro Shinkai; Fuminori Hyodo; Kiyoko Kato; Fumito Wada; Tsuyoshi Yamamoto; Mariko Harada-Shiba; Satoshi Obika; Kenji Nakano (Elsevier, 2017)
Y-box binding protein-1 (YB-1), involved in cancer progression and chemoradiation resistance, is overexpressed in not only cancer cells but also tumor blood vessels. In this study, we investigated the potential value of amido-bridged nucleic acid (AmNA)-modified antisense oligonucleotides (ASOs) targeting YB-1 (YB-1 ASOA) as an antiangiogenic cancer therapy. YB-1 ASOA was superior to natural DNA-based ASO or locked nucleic acid (LNA)-modified YB-1 ASO in both knockdown efficiency and safety, the latter assessed by liver function. YB-1 ASOA administered i.v. significantly inhibited YB-1 expression in CD31-positive angiogenic endothelial cells, but not in cancer cells, in the tumors. With regard to the mechanism of its antiangiogenic effects, YB-1 ASOA downregulated both Bcl-xL/VEGFR2 and Bcl-xL/Tie signal axes, which are key regulators of angiogenesis, and induced apoptosis in vascular endothelial cells. In the xenograft tumor model that had low sensitivity to anti-VEGF antibody, YB-1 ASOA significantly suppressed tumor growth; not only VEGFR2 but also Tie2 expression was decreased in tumor vessels. In conclusion, YB-1/Bcl-xL/VEGFR2 and YB-1/Bcl-xL/Tie signal axes play pivotal roles in tumor angiogenesis, and YB-1 ASOA may be feasible as an antiangiogenic therapy for solid tumors.